Respuesta :

leena

Hello! :)

[tex]y = -\frac{cos^{4}(x)}{4} + C[/tex]

Use u-substitution to solve for the indefinite integral:

[tex]\int cos^{3}(x)sin(x)dx[/tex]

Allow "u" to be the expression with an exponent:

[tex]u = cos(x)\\\\du = -sin(x)dx[/tex]

[tex]-du = sin(x)dx[/tex]

In the integral, we are missing a negative symbol (du = -sin(x)), so we can adjust the integral to accommodate this.

Substitute "u" for cos(x) and du for -sin(x):

[tex]-\int u^{3}du[/tex]

Use the integral power rule to solve:

[tex]\int x^{n} = \frac{x^{n + 1}}{n + 1}[/tex]

[tex]-\int u^{3}du = -[\frac{u^{4}}{4} ][/tex]

Add the constant "C" as this is an indefinite integral:

[tex]= -[\frac{u^{4}}{4} ] + C[/tex]

Substitute in the value of u (cos(x)) into the equation:

[tex]= -\frac{cos^{4}(x)}{4} + C[/tex]

And you're done!

ACCESS MORE